2022
DOI: 10.2460/javma.20.11.0615
|View full text |Cite
|
Sign up to set email alerts
|

Good prognosis for survival to hospital discharge in a group of horses with uterine prolapse treated at a veterinary medical teaching hospital

Abstract: OBJECTIVE To describe uterine prolapse, predispositions, and outcomes in mares treated between 1988 and 2019. ANIMALS 24 mares with uterine prolapse. PROCEDURES Clinical records were retrospectively reviewed, and follow-up information was gathered. The Mann-Whitney U test and Fisher exact test were used to analyze results for history and outcome variables for potential association with mare survival to hospital discharge. The χ2 test was used to compare breed distribution. RESULTS Age was known in 23 mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In this retrospective study , Jenny Boye and co‐workers at the University of California‐Davis, USA, described uterine prolapse, predispositions and outcomes in mares .…”
Section: Uterine Prolapse Outcomesmentioning
confidence: 99%
“…In this retrospective study , Jenny Boye and co‐workers at the University of California‐Davis, USA, described uterine prolapse, predispositions and outcomes in mares .…”
Section: Uterine Prolapse Outcomesmentioning
confidence: 99%
“…The article by Boye et al 6 is the first retrospective study of multiple cases of mare uterine prolapse. They found that Arabian mares were overrepresented and that there was no association between uterine prolapse and parity.…”
Section: Large Animalsmentioning
confidence: 99%